Bacterial interactions during sequential degradation of cyanobacterial necromass in a sulfidic arctic marine sediment. (3rd September 2018) - Müller, Albert L.; Pelikan, Claus; de Rezende, Julia R.; Wasmund, Kenneth; Putz, Martina; Glombitza, Clemens; Kjeldsen, Kasper U.; Jørgensen, Bo Barker; Loy, Alexander
Summary: Seafloor microorganisms impact global carbon cycling by mineralizing vast quantities of organic matter (OM) from pelagic primary production, which is predicted to increase in the Arctic because of diminishing sea ice cover. We studied microbial interspecies‐carbon‐flow during anaerobic OM degradation in arctic marine sediment using stable isotope probing. We supplemented sediment incubations with 13 C‐labeled cyanobacterial necromass (spirulina), mimicking fresh OM input, or acetate, an important OM degradation intermediate and monitored sulfate reduction rates and concentrations of volatile fatty acids (VFAs) during substrate degradation. Sequential 16S rRNA gene and transcript amplicon sequencing and fluorescence in situ hybridization combined with Raman microspectroscopy revealed that only few bacterial species were the main degraders of 13 C‐spirulina necromass. Psychrilyobacter, Psychromonas, Marinifilum, Colwellia, Marinilabiaceae and Clostridiales species were likely involved in the primary hydrolysis and fermentation of spirulina. VFAs, mainly acetate, produced from spirulina degradation were mineralized by sulfate‐reducing bacteria and an Arcobacter species. Cellular activity of Desulfobacteraceae and Desulfobulbaceae species during acetoclastic sulfate reduction was largely decoupled from relative 16S rRNA gene abundance shifts. Our findings provide new insights into the identities and physiological constraints that determine the population dynamics of key microorganisms during complex OM degradation in arctic marine sediments.© 2018 Society for Applied Microbiology and John Wiley & Sons Ltd